Historical aspects of the formation of national plant varietal resources in Ukraine - Leschuk, N. V.; Melnyk, S. I.; Marchenko, T. M.; Kokhovska, I. V.; Sytnyk, V. G. (Plant varieties studying and protection, 2022)
Introduction. National varietal plant resources are of particular importance for the economic development of Ukraine, because they ensure the stability of the crop industry as a component of the country’s food security. The analysis of the historiography of the development of the state variety testing since 1923 showed the lack of a systematic study of the formation of the State Register of Plant Varieties suitable for distribution in Ukraine (hereinafter – the Register of Plant Varieties of Ukraine). Purpose. To reveal the historical stages of the formation of national plant varietal resources, and substantiate the concept of their development. Methods. A collection of commonly known plant varieties that are or were in commercial circulation. Research methods – general scientific: hypothesis, observation, analysis, synthesis method for drawing conclusions; source study database with elements of extrapolation, which is formed based on the results of field, laboratory and analytical research. Results. The study of the history of state variety testing regulation made it possible to find out that the variety testing netork in Ukraine was established in 1923. The refore, the formation of national varietal plant resources has its own almost a hundred-year history. At all historical stages of the formation of national varietal resources, a variety with a complex of its morphobiological and economically valuable characteristics remains the subject of the research. State registration of a variety or rights to it ensures the commercial circulation of the variety. Identification of plant varieties, as the basis for varietal certification, increases the turnover of varieties on the market, ensures the growth of production volumes and improves the quality of crop products. Plant varieties distributed on the territory of Ukraine correspond to the criteria of distinctness, uniformity and stability generally accepted in international practice; meet the needs of consumers in terms of economically valuable characteristics; do not threaten the environment and human health. The formation of national plant varietal resources takes place in stages with the tendency to increase the economically valuable criteria, which ensures the competitiveness of the modern market of varieties and seeds in accordance with international requirements. Conclusions. The formation of plant varietal resources to meet the needs of consumers and/or breeding practice in Ukraine took place due to rather long historical stages of development and introduction of plant diversity, forms, criteria and methodology of varietal testing in time and space. The substantiation of the historical aspects of the concept of the varietal resources formation will allow optimizing the structure of the variety testing network, organizational foundations of the state registration of varieties and the protection of breeder’s rights. Вступ. Національні сортові рослинні ресурси мають особливе значення для економічного розвитку України, адже вони забезпечують стабільність галузі рослинництва як складової продовольчої безпеки держави. Аналіз історіографії розвитку державного сортовипробування з 1923 року показав відсутність системного дослідження формуванняя Державного реєстру сортів рослин, придатних для поширення в Україні (далі – Реєстр сортів рослин України). Мета. Розкрити історичні етапи формування національних рослинних сортових ресурсів, та обгрунтувати концепцію їхнього розвитку. Методи. Колекція загальновідомих сортів рослин, які перебувають чи перебували в комерційному обігу. Методи досліджень – загальнонаукові: гіпотеза, спостереження, аналіз, метод синтезу для формування висновків; джерелознавча база даних з елементами екстрополяції, яка формується за результатами польового, лабораторного та аналітичного дослідження. Результати. Дослідження історії регулювання державного сортовипробування дало змогу з’ясувати, що сортовипробувальна мережа в Україні була створена в 1923 році. Тому формування національних рослинних сортових реурсів має свою майже стодлітню історію. На всіх історичних етапах формування національних рослинних сортових ресурсів предметом дослідження залишається сорт з комплексом своїх морфобіологічних та господарсько-цінних характеристик. Державна реєстрація сорту або прав на нього забезпечує комерційний обіг сорту. Ідентифікація сортів рослин як основа сортової сертифікації збільшує обіг сортів на ринку, забезпечує зростання обсягів виробництва та підвищення якості продукції рослинництва. Сорти рослин, поширені на території України, відповідають загальноприйнятим у міжнародній практиці критеріям відмінності, однорідності та стабільності; задовольняють потреби споживачів за господарсько-цінними характеристиками; не загрожують довкіллю і здоров’ю людини. Формування національних рослинних сортових ресурсів відбувається поетапно з тенденцією підвищення господарсько-цінних критеріїв, що забезпечує конкурентність сучасного ринку сортів і насіння відповідно до міжнародних вимог. Висновки. Формування рослинних сортових ресурсів для задоволення потреб споживачів та/або селекційної практики в Україні відбувалось завдяки доволі тривалим історичним етапам розвитку та інтродукції рослинного різноманіття, форм, критеріїв і методології сортовипробувальної справи в часі і просторі. Об´рунтування історичних аспектів концепції формування сортових ресурсів дозволить оптимізувати структуру сортовипробувальної мережі, організаційні основи державної реєстрації сортів та охорони прав селекціонера.